Pengembangan Game KEBAL berbasis Web App sebagai Penguatan Sikap Toleransi Siswa Kelas 4A SDIT Al-Akbar Kabupaten Blitar - Munawaroh, Latifatul; Alfi, Cindya; Fatih, Mohamad (Universitas Nusantara PGRI Kediri, 2024)
This study aims to determine how the validity, feasibility of KEBAL media based on Web App and also the strengthening of tolerance attitudes of 4A class students of SDIT Al Akbar Blitar Regency. This research uses the Borg and Gall development model with trials at SDIT Al Akbar Blitar Regency. The data collection techniques used are interviews, questionnaires and documentation. The validation results show that the Web App-based KEBAL product has a very high level of validity and feasibility. The validity of this product was assessed by media experts and material experts while the feasibility of the product was assessed by the class teacher through a questionnaire. The product trial was carried out with 2 stages, namely small scale and large scale and obtained a score of 90% and 92% with a very tolerant category. Thus the product that has been made can be used without revision.